The musketeers. [The complete first season] [videorecording (DVD)] - Cabrera, Santiago; Capaldi, Peter; Charles, Howard, 1983-; Dumas, Alexandre, 1802-1870 (BBC Worldwide Americas, 2014)
On the streets of seventeenth century Paris, law and order is an idea more than a reality. In addition to being King Louis XIII's personal bodyguards, Athos, Aramis, Porthos, and their new friend D'Artagnan, stand resolutely for social justice, honor, valor, love, and for the thrill of it all. They must fight to maintain order and protect their King and Queen against the worst intentions of the ruthless Cardinal Richelieu and his secret weapon, Milady.